Government debt and stock price crash risk: International Evidence - Hamdi, Ben-Nasr (2024)
We add to the literature on the economic outcomes of government debt and argue that government debt increases crash risk via two channels: (i) hoarding bad news and (ii) tax avoidance. Based on a large international sample, our results indicate that stock crash risk is positively associated with government debt. Our conclusions are robust when we treat endogeneity issues, and our tests confirm the validity of bad news hoarding and tax avoidance as channels through which government debt influences stock price crash risk.